Toward mapping spatiotemporal characteristics of muscle oxygenation in different motor modalities by multichannel near‐infrared spectroscopy. (29th April 2019) - Cui, Han; Geng, Yanjuan; Samuel, Oluwarotimi Williams; Jiang, Naifu; Guo, Kaifeng; Huang, Zhen; Li, Guanglin
Summary: Commonly, the near‐infrared spectroscopy (NIRS) devices are used to measure muscle oxygenated hemoglobin (HBO) concentration and total hemoglobin (HBT) concentration with a single channel, which can obtain the temporal HBO and HBT signals. Lacking of the spatial information of muscle oxygenation will limit the exploration of the heterogeneity of muscle activities. In this study, a multichannel NIRS recording system was used to measure the muscle oxygenation with an attempt to simultaneously provide the temporal and spatial HBO and HBT concentration. In the experiment, the influences of four motor tasks, including active, passive, imaginary movement, and the control task (no movement), on muscle oxygenation were investigated in eight normal subjects. Our results showed that both amplitude and spatial heterogeneity associated with variation in muscle oxygenation during active and passive motor tasks were significantly different between the motor time and rest time ( P  < 0.05). Furthermore, the region where HBO concentration decreased during the active motor task was in accordance with the anatomical position of contracted muscle, which cannot be observed from the results of the passive task. Considering the imaginary and control tasks in which the muscle was in a fixed/stationary state, the amplitude and spatial heterogeneity associated with variations in muscle oxygenation only exhibited slight changes ( P  > 0.05). This pilot study suggested that the spatiotemporal information obtained from multichannel NIRS devices might be potential for accurate measurement of the variation in muscle oxygenation during motor tasks, which would be useful for different clinical applications.